Peran Inaportnet Dalam Proses Penerbitan Surat Persetujuan Berlayar (SPB) Online di Kantor Kesyahbandaran dan Otoritas Pelabuhan Kelas III Manado - Nastasia Inri Putri Pongsituru; Yustiani Frastica; Stevian G.A. Rakka; Azhar Ariansyah Ansar (Politeknik Pelayaran Sulawesi Utara, 2024)
This study aims to analyze the impact of Inaportnet implementation on the process of issuing the Sailing Approval Letter (SPB) online at the Class III Manado Port Authority and Harbor Master's Office. Inaportnet is an internet-based system designed to facilitate and expedite the shipping administration process, with the goal of improving efficiency and transparency in port services. This research uses a descriptive method with a qualitative approach, involving data collection through interviews with port officials and service users, as well as direct field observations.The results of the study indicate that the implementation of Inaportnet has a significantly positive impact on the SPB issuance process. The use of this system successfully speeds up processing time, reduces excessive bureaucracy, and enhances transparency and accountability in services. However, the study also found some challenges in its implementation, such as technical issues with the system, lack of supporting infrastructure, and the need for further training for involved staff. Therefore, to optimize the benefits of Inaportnet, it is recommended to improve technological infrastructure, provide regular training for staff, and conduct routine monitoring and evaluation of the system's performance.